PENGARUH LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN TERHADAP KUALITAS HASIL AUDIT - Asri Fitri Annisa; Dirvi Surya Abbas; Hesty Ervianni Zulaecha; Imam Hidayat (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to examine the effect of leverage, company size profitability on the quality of audit results in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The research time period used is 5 years, namely the 2016-2021 period. The research population includes several sub-sector manufacturing companies and are listed on the stock exchange in the 2017-2021 period. The sample taken by this study used a purposive sampling method and had predetermined criteria, namely 10 companies